Citizenship skills and their educational policies in Latin America and Colombia - Montaña Contreras, Deiscy; López Guio, Angela Andrea (Uptc, 2021)
This article shows an overview on citizenship competencies and public policies in Colombia and other Latin American countries, by compiling articles and analyzing the discourses of competencies as common knowledge. From a methodological perspective, categories such as: competencies, education, and public policies were tracked and conceptualized. The study was performed in three stages: the first was a historical and conceptual approach to citizenship competencies from the 80’s in Colombia and from the enactment of the Constitution in 1991; the second dealt with the concept of citizenship which was studied from the connection of theoretical discourse and experiences in classroom of different Spanish-speaking countries; and finally, the implications that the neoliberal model has had both in educational policies and in the formation of citizens and their intervention in higher education were evaluated. As a result, in the analysis of the category of public policies and citizenship competencies, there is an important concern to link in an articulated and permanent manner the educational curriculum and the guidelines established by governmental entities to the application and regulation of such competencies, not as just another lecture in the educational institutions established for the labor market, but as a fundamental formative component for the construction of citizenship, without falling into the instrumentalization and ambiguity of the notion of competencies and citizenship in the current educational environment.